Kemampuan Menelaah Unsur Dan Kaidah Kebahasaan Teks Drama Menggunakan Model Make A Match Siswa Kelas VIII SMPN 1 Hamparan Perak - Fira Febriyanti,; Trisnawati Hutagalung, (Jurnal Bintang Pendidikan Indonesia, 2024)
This research is motivated by the ability to examine the elements and language rules of students' drama texts is still low, students' lack of interest in studying drama texts, the use of learning models that are less attractive and monotonous, the learning process that takes place still uses a teacher-centered model and low student scores, average The average obtained by students is 65. The purpose of this research is as follows. 1) To analyze the elements and language rules of drama texts for class VIII students of SMP Negeri 1 Hamparan Perak before using the Make a Match learning model. 2) To analyze the ability to examine the elements and language rules of drama text for class VIII students of SMP Negeri 1 Hamparan Perak for the 2022/2023 Academic Year after using the Make a Match learning model. This type of research is experimental research with a quantitative approach. The design in the research used is the One-Group Pretest-Posttest Design, in this design there is a Pretest before being given treatment and a Posttest after being given treatment. The research results at the time of the pretest obtained an average of 63, and entered into the sufficient category. While the results of the posttest research obtained an average value of 79.8 and included in the good category. It can be concluded that class VIII students of SMPN 1 Hamparan Perak are able to examine the elements and language rules of drama texts using the Make a Match model.